A cluster randomised trial of a school-based intervention to prevent decline in adolescent physical activity levels: study protocol for the 'Physical Activity 4 Everyone' trial - Sutherland Rachel; Campbell Elizabeth; Lubans David R; Morgan Philip J; Okely Anthony D; Nathan Nicole; Wolfenden Luke; Jones Jannah; Davies Lynda; Gillham Karen; Wiggers John (BMC, 2013)
Abstract Background Adolescence is an established period of physical activity decline. Multi-component school-based interventions have the potential to slow the decline in adolescents' physical activity; however, few interventions have been conducted in schools located in low-income or disadvantaged communities. This study aims to assess the effectiveness of a multi-component school-based intervention in reducing the decline in physical activity among students attending secondary schools located in disadvantaged communities. Methods/Design The cluster randomised trial will be conducted with 10 secondary schools located in selected regions of New South Wales, Australia. The schools will be selected from areas that have a level of socio-economic status that is below the state average. Five schools will be allocated to receive an intervention based on the Health Promoting Schools framework, and will be supported by a part-time physical activity consultant placed in intervention schools who will implement a range of intervention adoption strategies. Study measures will be taken at baseline when students are in Year 7 (12-13 years) and again after 12- and 24-months. The primary outcome, minutes of moderate- to-vigorous- intensity physical activity per day and percentage of time in moderate- to vigorous-intensity physical activity (MVPA), will be objectively assessed using accelerometers (Actigraph GT3x+). Group allocation and intervention delivery will commence after baseline data collection. The intervention will continue during school terms through to 24-month follow-up. Discussion The study will provide evidence regarding the effectiveness of a multi-component school-based intervention that includes an in-school physical activity consultant targeting the physical activity levels of adolescents in disadvantaged Australian secondary schools. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12612000382875.